(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Far Eastern Federal University, Vladivostok In this article “soft power” national strategies in the foreign policy of the USA, China and Russia are considered. The main approaches, resources, instruments, goals and results of using the “soft power” at present time are analyzed. The national “soft power” strategies based on using the foreign policy of non-military instruments of influence, demonstrate the conceptual views of states to the “desired structure of the world” and can be analyzed by a variety of criteria. Key words: “soft power”, national strategy, balance of power, foreign policy, public diplomacy, cultural attractiveness.